Physical Treatments and Propolis Extract to Enhance Quality Attributes of Fresh-Cut Mixed Vegetables - Alvarez, María Victoria (2017)
The impact of individual and combined application of propolis extract (PE) plus ultrasound (ULT) or thermal treatment (TT) on the microbiological, nutritional, physicochemical and sensory quality of fresh-cut mixed vegetables for soup (celery, leek and butternut squash) stored at 5C was studied. The use of PE slightly reduced microbial growth, inhibited the activity of browning related enzymes and improved quality attributes during refrigerated storage. Moreover, PE was effective to reduce ascorbic acid losses in the product maintaining its nutritional quality. TT greatly lowered the initial microbial load (1.7–2.2 log units) and also reduced microbial growth on mixed vegetables extending its microbiological shelf-life to 5 days. Furthermore, TT inactivated browning enzymes improving visual quality; however, ascorbic acid degradation adversely affected nutritional quality. Meanwhile, ULT caused a significant microbial inactivation, reduced browning enzyme activity and also the inhibitory effect on polyphenoloxidase enzyme was enhanced by combining ULT with PE. Practical Applications: The use of natural agents, as propolis extract, along with physical treatments to preserve the quality of fresh-cut mixed vegetables for soup might be an interesting option to address the concerns of the consumer about the use of synthetic chemical antimicrobials potentially harmful for health.